MR Imaging, Single-photon Emission CT, and Neurocognitive Performance after Mild Traumatic Brain Injury - Hofman, Paul A.M.; Stapert, Sven Z.; van Kroonenburgh, Marinus J.P.G.; Jolles, Jelle; de Kruijk, Jelle; Wilmink, Jan T. (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: Mild traumatic brain injury (mTBI) (Glasgow Coma Scale = 14–15) is a common neurologic disorder and a common cause of neurocognitive deficits in the young population. Most patients recover fully from mTBI, but 15% to 29% of patients have persistent neurocognitive problems. Although a partially organic origin is considered likely, little brain imaging evidence exists for this assumption. The aims of the present study were to establish the prevalence of posttraumatic lesions in mTBI patients on MR images and to assess the relation between these imaging findings and posttraumatic symptoms. Secondly, we explored the value of early posttraumatic single-photon emission CT (SPECT) for the evaluation of mTBI.METHODS: Twenty-one consecutive patients were included in the study. Patients underwent MR examination, technetium-99m hexamethylpropylene amine oxime SPECT, and neurocognitive assessment within 5 days after injury. Neurocognitive follow-up was conducted 2 and 6 months after injury, and MR imaging was repeated after 6 months. Lesion size and brain atrophy were measured on the MR studies.RESULTS: Twelve (57%) of 21 patients had abnormal MR findings, and 11 (61%) of 18 had abnormal SPECT findings. Patients with abnormal MR or SPECT findings had brain atrophy at follow-up. The mean neurocognitive performance of all subjects was within normal range. There was no difference in neurocognitive performance between patients with normal and abnormal MR findings. Patients with abnormal MR findings only showed significantly slower reaction times during a reaction-time task. Seven patients had persistent neurocognitive complaints and one patient met the criteria for a postconcussional syndrome.CONCLUSION: Brain lesions are common after mTBI; up to 77% of patients may have abnormal findings either on MR images or SPECT scans, and these lesions may lead to brain atrophy. The association between hypoperfusion seen on acute SPECT and brain atrophy after 6 months suggests the possibility of (secondary) ischemic brain damage. There is only a weak correlation between neuroimaging findings and neurocognitive outcome.